High-Resolution Translatome Analysis Reveals Cortical Cell Programs During Early Soybean Nodulation - Song, Jae Hyo; Montes-Luz, Bruna; Tadra-Sfeir, Michelle Zibetti; Cui, Yaya; Su, Lingtao; Xu, Dong; Stacey, Gary (Frontiers in Plant Science, 2022)
Nodule organogenesis in legumes is regulated temporally and spatially through gene networks. Genome-wide transcriptome, proteomic and metabolomic analyses have been used previously to define the functional role of various plant genes in the nodulation process. However, while significant progress has been made, most of these studies have suffered from tissue dilution since only a few cells/ root regions respond to rhizobial infection, with much of the root non-responsive. To partially overcome this issue, we adopted TRAP (translating ribosome affinity purification) to specifically monitor the response of the root cortex to rhizobial inoculation using a cortex-specific promoter. While previous studies have largely focused on the plant response within the root epidermis (e.g., root hairs) or within developing nodules, much less is known about the early responses within the root cortex, such as in relation to the development of the nodule primordium or growth of the infection thread. We focused on identifying genes specifically regulated during early nodule organogenesis using roots inoculated with Bradyrhizobium japonicum. A number of novel nodulation gene candidates were discovered, as well as soybean orthologues of nodulation genes previously reported in other legumes. The differential cortex expression of several genes was confirmed using a promoter-GUS analysis, and RNAi was used to investigate gene function. Notably, a number of differentially regulated genes involved in phytohormone signaling, including auxin, cytokinin, and gibberellic acid (GA), were also discovered, providing deep insight into phytohormone signaling during early nodule development.